Akibat Hukum Pelaksanaan Kawin Lari yang Tidak Disetujui Wali Nikah Diyinjau Dari Undang-Undang Nomor 1 Tahun 1974 - Hani, Tantri Ummu; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law No. 1 of 1974 on Marriage also regulates the legitimacy of a marriage. The existence of a legal marriage, the child born shall be a valid child, in the sense that if the marriage is done lawfully according to the religion and applicable law, then its existence and all its consequences will be accepted and acknowledged legally by the public as well nation and state. The purpose of writing this thesis, namely: First how the implementation of elopment marriage not approved by the guardian of marriage in view of Law Number 1 Year 1974 Second how the legal effect of marriage. Implementation not approved marriage guardian in terms of Marriage Act No. 1 of 1974 on Marriage. This type of investigation can be categorized into a sociological juridical research type. Because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Matur sub-district, while the population and sample were all parties related to the problem studied in this research. Sources of data used, primary data, secondary data and tertiary data, data collection techniques in this study by observation, interview and literature study. Conclusion Implementation of marriage which is not approved by marriage guardian from Law Number 1 Year 1974 that basically Kawin Lari is actually still in the category of siri marriage, because the implementation is done secretly or secretly. However, the marriage guardian in this case is an unlawful guardian, as well as the witness and employee of the marriage recorder. Due to the law of the implementation of elopment which is not approved by marriage guardian from marriage law No. 1 year 1974 about marriage is always find problem in state administration, can not legalize marriage book in office of KUA, country does not recognize marriage of married couple who make elopement, The couple eloped did not get public service in government institution because it was done illegally due to the absence of legal guardian therefore any form of legal relationship related to marriage administration can not be done. But if there is no objection then the men just enough to pay a fine or substitute money according to violations committed against the election rules, and on the size of the fine will be decided by consensus mufakat which is confidential by both parties.Keywords : Marriage, run marriage, marriage guardian